Mitochondrial-targeted therapies in traumatic brain injury: From bench to bedside - Sidra Tabassum; Silin Wu; Chang-Hun Lee; Bosco Seong Kyu Yang; Aaron M. Gusdon; Huimahn A. Choi; Xuefang S. Ren (Neurotherapeutics, 2025)
Traumatic brain injury (TBI) is a leading cause of morbidity and mortality worldwide, with limited effective therapeutic options currently available. Recent research has highlighted the pivotal role of mitochondrial dysfunction in the pathophysiology of TBI, making mitochondria an attractive target for therapeutic intervention. This review comprehensively examines advancements in mitochondrial-targeted therapies for TBI, bridging the gap from basic research to clinical applications. We discuss the underlying mechanisms of mitochondrial damage in TBI, including oxidative stress, impaired bioenergetics, mitochondrial dynamics, and apoptotic pathways. Furthermore, we highlight the complex interplay between mitochondrial dysfunction, inflammation, and blood-brain barrier (BBB) integrity, elucidating how these interactions exacerbate injury and impede recovery. We also evaluate various preclinical studies exploring pharmacological agents, gene therapy, and novel drug delivery systems designed to protect and restore mitochondrial function. Clinical trials and their outcomes are assessed to evaluate the translational potential of mitochondrial-targeted therapies in TBI. By integrating findings from bench to bedside, this review emphasizes promising therapeutic avenues and addresses remaining challenges. It also provides guidance for future research to pave the way for innovative treatments that improve patient outcomes in TBI.